Correction: Abd Algaffar et al. Sandalwood Oils of Different Origins Are Active In Vitro against Madurella mycetomatis, the Major Fungal Pathogen Responsible for Eumycetoma. Molecules 2024, 29, 1846 - Shereen O. Abd Algaffar; Stephan Seegers; Prabodh Satyal; William N. Setzer; Thomas J. Schmidt; Sami A. Khalid (Molecules)
In the original publication [...]